Implementing an Agile Document Management System to Improve Efficiency and Compliance in the Cargo Industry - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research addresses efficiency and compliance issues in the cargo industry by implementing an Agile-based document management sys-tem. Common problems encountered, such as inefficient manual pro-cesses and the risk of document loss, are the main focus. The stages of system development, including requirements definition, planning, de-velopment, testing, and implementation, were analyzed in depth with an Agile methodology approach. The system could meet the expected functional, security, and performance needs through a series of tests. The results show the vital contribution of the Agile approach in im-proving efficiency and compliance in the cargo industry by implement-ing a document management system that is adaptive, efficient, and compliant with industry standards.